ANALISIS PEARLS SEBAGAI ALAT UKUR KINERJA KEUANGAN PADA CREDIT UNION DAYA LESTARI (Studi Kasus Credit Union Daya Lestari di Kota Samarinda) - Agusta Maria Mala’ang; Muhammad Zaini; Eko Adi Widyanto (JEMBA: JURNAL EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2023)
This study aims to determine the level of soundness in the financial performance of Credit Unions based on indicators in the PEARLS analysis over a period of 2 years. This study uses documentary data on financial performance in the form of factors, journals and financial reports. Data collection was carried out using literature study and documentation techniques. The data analysis technique used to answer this analysis is using the PEARLS indicator system. The results showed that the financial performance of Credit Union Daya Lestari in terms of indicators (1) Protection P1 and P2 showed unhealthy performance; (2) Effective financial structure showed unhealthy performance on indicators E1, E5, E6 and E9, there was one healthy indicators, namely in E1 in 2018-2019; (3) Asset quality shows unhealthy performance in indicators A1 and A2, there are healthy indicators, namely in A2 in 2017 and 2019; (4) Rates of return and costs show performance unhealthy; (5) Liquidity shows unhealthy performance; (6) Signs of growth shows unhealthy performance